2015
DOI: 10.1093/protein/gzv032
|View full text |Cite
|
Sign up to set email alerts
|

An efficient protocol towards site-specifically clickable nanobodies in high yield: cytoplasmic expression inEscherichia colicombined with intein-mediated protein ligation

Abstract: In this study, several expression strategies were investigated in order to develop a generic, highly productive and efficient protocol to produce nanobodies modified with a clickable alkyne function at their C-terminus via the intein-mediated protein ligation (IPL) technique. Hereto, the nanobody targeting the vascular cell adhesion molecule 1 (NbVCAM1) was used as a workhorse. The highlights of the protocol can be ascribed to a cytoplasmic expression of the nanobody-intein-chitin-binding domain fusion protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 74 publications
2
31
0
1
Order By: Relevance
“…2). Other researchers have also reported recombinant protein yield increases when using EnPresso ® B compared to LB broth (Ta et al 2015;Zarschler et al 2013). The ratio of protein yield per cell was, however, similar for EnPresso ® B medium and LB broth.…”
Section: Discussionmentioning
confidence: 77%
“…2). Other researchers have also reported recombinant protein yield increases when using EnPresso ® B compared to LB broth (Ta et al 2015;Zarschler et al 2013). The ratio of protein yield per cell was, however, similar for EnPresso ® B medium and LB broth.…”
Section: Discussionmentioning
confidence: 77%
“…Recombinant expression of VHH can produce single domain antibody (sdAb) with dimensions in the nanometer range, which is also known as nanobody (Nb). High expression yield of Nbs can be obtained in various expression systems, such as bacteria, fungi and plants [1012]. …”
Section: Introductionmentioning
confidence: 99%
“…This strategy became available 30 years ago, applied to different recombinant proteins which require disulfide bonds to fold into their native structure and progressively improved with the introduction of more efficient strains such as Rosetta-gami B (DE3) or SHuffle T7 cells. These have been used for the cytoplasmic production of naked nanobodies [110,111] and of their fusion variants containing at their Cterminus an intein-chitin domain suitable for site-specific alkyne functionalization that requires reducing conditions for its functionality [109,112,113]. In one case it was confirmed that the binding properties of the non-modified nanobodies produced in the periplasm were preserved when the same binders were expressed as fusion reagents in the cytoplasm of Shuffle T7 cells [109].…”
Section: Bacterial Cytoplasmmentioning
confidence: 91%